At the Origins of Abovian’s Poetry - SAFARYAN, VAZGEN (Bulletin of Yerevan University B: Philology, 2021)
Khachatur Abovian preserved the medieval peculiarities of the genre in the classical (Old Armenian) poems prior to the Dorpat years. The classical poems at the Dorpat years contained visual elements of European poetry. The aim of being comprehensible to people led the writer to simple and coherent representations. Western elegy and ode are combined with eastern ‘bayati’ (sorrowful music). Even though the classical works continued to be composed, the refined and rich Old Armenian referred as literary language, remained the liaison between Armenian high cultural past and European analogous present for Abovian.